1984
DOI: 10.1172/jci111486
|View full text |Cite
|
Sign up to set email alerts
|

Response of hepatic mitochondrial alpha-glycerophosphate dehydrogenase and malic enzyme to constant infusions of L-triiodothyronine in rats bearing the Walker 256 carcinoma. Evidence for divergent postreceptor regulation of the thyroid hormone response.

Abstract: Aatract. To characterize the hepatic response to L-triiodothyronine (T3) in an experimental nonthyroidal disease, we determined the activity of hepatic mitochondrial a-glycerophosphate dehydrogenase (a-GPD) and cytosol malic enzyme (ME) as a function of the saturation of the nuclear T3 receptor during constant T3 infusions in rats bearing the Walker 256 carcinoma. Groups of control and tumor-bearing rats were infused by minipumps (Alza Corp., Palo Alto, CA) with vehicle, 1.2 or 4.5 Ag T3/100 body wt per day fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
12
0

Year Published

1985
1985
2006
2006

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 43 publications
4
12
0
Order By: Relevance
“…Mean T3 receptor concentration of liver nuclei from tumor rats, 0.35 ± 0.04 fmol/p-g DNA, was 50 ± 6% of that measured in control rats, 0.70 ± 0.10 fmol/p,g DNA. These findings are in accord with previous reports from our laboratory (14). We have also reported that the abundance of TR in anterior pituitary of tumor rats is decreased to nearly the same extent as demonstrated here for liver.…”
Section: Resultssupporting
confidence: 94%
See 4 more Smart Citations
“…Mean T3 receptor concentration of liver nuclei from tumor rats, 0.35 ± 0.04 fmol/p-g DNA, was 50 ± 6% of that measured in control rats, 0.70 ± 0.10 fmol/p,g DNA. These findings are in accord with previous reports from our laboratory (14). We have also reported that the abundance of TR in anterior pituitary of tumor rats is decreased to nearly the same extent as demonstrated here for liver.…”
Section: Resultssupporting
confidence: 94%
“…In rat liver, the activity of two enzymes, mitochondrial a-glycerophosphate dehydrogenase (a-GPD) and cytosolic malic enzyme (ME) are typically induced by T3. In rats bearing the Walker 256 tumor, a-GPD activity revealed heightened sensitivity to induction of T3 whereas the induction of ME activity by T3 was depressed (14). We have also shown similar differential regulation in the anterior pituitary of tumor animals (15).…”
Section: Discussionsupporting
confidence: 72%
See 3 more Smart Citations